History and Symbolic Meaning of Tongkonan from the Views of the Tana Toraja People - Aziawatia, Nur; Yagdhon Alfani, Syafiq; Sasa Dillah, Putri; Saputra, Dian; Cindy Pramasta, Ni Komang (Dharmahita: Journal of Community Service and Development, 2024)
This research explores the history, significance, and symbolic meanings of Tongkonan, the traditional house of the Toraja people. Through interviews with stakeholders of Toraja society and a review of relevant literature, the study aims to uncover the deep-rooted connections between Tongkonan and social status, as well as its role in upholding traditional laws. The findings underscore Tongkonan's central importance as not merely architectural structures but repositories of cultural identity and sacred rituals such as Rambu Solo', Rambu Tuka', and Mangrara. These houses are believed to have originated in heaven, reflecting the profound ancestral reverence among the Toraja. The intricate details of Tongkonan design, including shapes, sizes, and motifs, highlight meticulous attention to cultural and philosophical nuances. The study suggests that Tongkonan remains indispensable to Toraja customs and identity, resisting pressures of modernization. This research contributes to preserving Toraja's cultural heritage by elucidating the enduring significance of Tongkonan in contemporary times.